Some Difficulties in translating English humour into Arabic - Dr.Nuri EL-Agell (مجلة كلية الاداب, 2022)
Introduction and what makes people laugh. Desi Humour is the ability to understand and enjoy what is people laugh. Despite the existence of universal humour as in a child making mature adult-like statement ssumed that some languages have their own characteristics istieally and culturally that evoke in their audience pleasurabi linguistically and and playful response. Menacere, M. (1991:36) tells us that As individuals view reality differently, it would be impossible to ask two different languages to express thoughts in similar manner because each one possesses a mode of expression using the linguistic devices available in the language according to its needs. This has its bearing on translation; however, in the case of similar cultures and languages it is often possible to have an effective translation (Raphelson-West, 1989: 129). The translation of English humour into other languages has been dealt with by Leibold ( 1989), Nilsen (1989) Ornstein-Galicia (1989) among others The purpose of this paper is to investigate and analyze English humour and demonstrate the difficulties encountered in rendering it